A rare case of acute mesenteric ischaemia and duodenal ulcer perforation together in a single patient in a tertiary care hospital - Ammar , Ahmed Siddique; Sattar, Zahara; Naqi, Syed Asghar; Hadi, Ali; Inayat, Farwa; Noor Ul Haq, Mahwish (Journal of the Pakistan Medical Association, 2022)
A 57 years old male presented in the emergency department of EAST Surgical Ward, MAYO Hospital Lahore in February 2021 with complaints of abdominal distension, pain and vomiting. He was a chronic smoker and diagnosed hypertensive for the last 14 years but was non-compliant with oral antihypertensive medications. He was a factory worker and took NSAIDs off and on for pain in the knee joint for the last five years. On examination, his abdomen was tense and tender with resonant percussion notes in the right hypogastrium and epigastrium. His chest x-ray showed free gas under the right diaphragm. Diagnosis of a perforated duodenal ulcer was made and exploratory laparotomy was done. Examination revealed a perforated ulcer in the first part of the duodenum with greenish gangrenous patches on the next 3 feet of the small gut. ---Continue